Strategi Komunikasi Pemasaran Terpadu Dinas Kebudayaan dan Pariwisata Kota Surakarta dalam Mempromosikan Event “Solo International Performing Arts (SIPA) 2024” - Devandra Dicky Kurniawan; Hasbullah Azis; Rahmat Wisudawanto (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
In promoting a cultural arts performance, the success of an event is determined not only by the quality of the performance itself but also by the effectiveness of the marketing communication strategy implemented. In today’s digital era, organizers of cultural art performances face increasingly complex challenges, including shifts in audience media consumption behavior, rapid developments in communication technology, and the need to build sustained digital engagement between organizers and stakeholders.This study adopts the Integrated Marketing Communication (IMC) theory to examine the marketing communication strategies implemented by the Department of Culture and Tourism of Surakarta City in promoting the Solo International Performing Arts (SIPA) event in 2024. The research methodology includes in-depth interviews with organizers and document analysis of promotional materials and publication activities.The findings indicate that the department applied eight elements of integrated marketing communication: advertising, sales promotion, events and experiences, public relations and publicity, direct marketing, interactive marketing, mobile marketing, and personal selling. Each element was carried out synergistically to build awareness, attract public interest, and shape a positive image of the SIPA event in society.The implemented strategy has successfully reached a broader audience through digital channels such as social media and official websites, as well as through direct approaches like local media publications and collaboration with art communities. However, challenges remain in delivering more innovative and creative promotional content to enhance the event’s appeal. These findings offer important implications for cultural event managers, emphasizing the need for structured, consistent, and audience-relevant promotional strategies in the digital era. A well-integrated marketing communication approach not only strengthens public engagement but also reinforces the identity and sustainability of cultural events like SIPA on both local and international levels.